Visualization Power BI Penggunaan Aplikasi Digides dengan Pemerataan Akses Internet di Jawa Barat - Slamet Ramadhani; Edita Toding Sirenden; Intan Listra Della Megoraya; Yasmin Amanda Putri (SPECTA Journal of Technology, 2022)
Internet technology has changed the face of world communication, which has long been dominated by non-computer digital devices, into global computer communications. This condition is considered to have good implications for the digital economy. However, the uneven distribution of the internet so that some districts are not covered by the internet network is a problem to support the existence of a Digital Village.. The research method used consists of several stages, including; define literature study, determine data, determine problems, data preparation, data warehouse, exploration of BI power, data visualization and implementation. The factor causing the lack of optimization of the use of the Digides Application is due to the lack of distribution of BTS and internet access in the city of West Java. The attitude and policies issued by the government towards the law governing the equitable distribution of quality village growth development in Law no. 6 of 2014 concerning Villages has provided Legal Standing and a strategic foundation for the development and empowerment of rural communities, towards independent and prosperous villages.